Ovarian Masses in Children and Adolescents: A Review of the Literature with Emphasis on the Diagnostic Approach - Effrosyni Birbas; Theofilos Kanavos; Fani Gkrozou; Chara Skentou; Angelos Daniilidis; Anastasia Vatopoulou (MDPI AG, 2023)
Most abdominal masses in the pediatric population derive from the ovaries. Ovarian masses can occur in all ages, although their incidence, clinical presentation and histological distribution vary among different age groups. Children and adolescents may develop non-neoplastic ovarian lesions, such as functional cysts, endometrioma, torsion, abscess and lymphangioma as well as neoplasms, which are divided into germ cell, epithelial, sex-cord stromal and miscellaneous tumors. Germ cell tumors account for the majority of ovarian neoplasms in the pediatric population, while adults most frequently present with epithelial tumors. Mature teratoma is the most common ovarian neoplasm in children and adolescents, whereas dysgerminoma constitutes the most frequent ovarian malignancy. Clinical manifestations generally include abdominal pain, palpable mass, nausea/vomiting and endocrine alterations, such as menstrual abnormalities, precocious puberty and virilization. During the investigation of pediatric ovarian masses, the most important objective is to evaluate the likelihood of malignancy since the management of benign and malignant lesions is fundamentally different. The presence of solid components, large size and heterogenous appearance on transabdominal ultrasonography, magnetic resonance imaging and computed tomography indicate an increased risk of malignancy. Useful tumor markers that raise concern for ovarian cancer in children and adolescents include alpha-fetoprotein, lactate dehydrogenase, beta subunit of human chorionic gonadotropin, cancer antigen 125 and inhibin. However, their serum levels can neither confirm nor exclude malignancy. Management of pediatric ovarian masses needs to be curative and, when feasible, function-preserving and minimally invasive. Children and adolescents with an ovarian mass should be treated in specialized centers to avoid unnecessary oophorectomies and ensure the best possible outcome.